PERSEPSI PENGGUNA E-COMMERCE TERHADAP KUALITAS INFORMASI PEMBELIAN BARANG DENGAN METODE PEMBAYARAN CASH ON DELIVERY (COD) BERDAMPAK PADA TERJADINYA PENGANCAMAN KEPADA KURIR JASA EXPEDISI - Marshelia Gloria Narida (Kinesik, 2021)
Purchasing goods with cash on delivery (COD) payment method is a service presented by Shopee to make it easier for buyers who don’t have mobile or internet banking. The buyer pays for the goods when the goods have arrived at the delivery address delivered by the expedition service courier. However, some shoppers vented their disquire to the couriers of the expedition service when the goods they received did not match what they ordered through the Shopee app. Informants in the study suggested that their perception of the quality of information Shopee provides related to COD is still inaccurate, not yet timely, not yet relevant and incomplete. Shopee is considered to still focus on favorable information, not information that educates buyers related to COD. Information that is not received by the buyer can trigger disappointed buyers to vent to the courier expedisi service. Shopee is advised to create information in the form of interesting visualizations, not with long sentences so that it is easy to understand. Information is placed on the display menu that is easily seen by the buyer as on the main page or the information appears when the buyer will check out the item. Good information can prevent disappointed buyers from doing acidification or violence to couriers.